2012
DOI: 10.1210/en.2011-2147
|View full text |Cite
|
Sign up to set email alerts
|

Early Mitochondrial Adaptations in Skeletal Muscle to Diet-Induced Obesity Are Strain Dependent and Determine Oxidative Stress and Energy Expenditure But Not Insulin Sensitivity

Abstract: This study sought to elucidate the relationship between skeletal muscle mitochondrial dysfunction, oxidative stress, and insulin resistance in two mouse models with differential susceptibility to diet-induced obesity. We examined the time course of mitochondrial dysfunction and insulin resistance in obesity-prone C57B and obesity-resistant FVB mouse strains in response to high-fat feeding. After 5 wk, impaired insulin-mediated glucose uptake in skeletal muscle developed in both strains in the absence of any im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
44
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 34 publications
7
44
0
Order By: Relevance
“…However, other observations report discrepant results, showing that high-fat feeding in rats was associated with no variation (Atgié et al 1993, De Feyter et al 2008a or even a higher mitochondrial capacity (Hancock et al 2008), and IR could be related to incomplete intramitochondrial β-oxidation (Koves et al 2008). Several studies show that insulin resistance arises when mitochondrial function is unaffected or even improved , Ara et al 2011, Boudina et al 2012, or conversely that impaired mitochondrial functioning alone does not cause insulin resistance (Wredenberg et al 2006). These latter findings data seem to indicate that, at least in rodents, consumption of high-fat diet is not always accompanied by mitochondrial dysfunction, but rather leads to improved mitochondrial oxidative capacity and/or biogenesis (Gómez-Pérez et al 2012, Wessels et al 2015, even in the presence of IR.…”
Section: Mitochondrial Dysfunction In Insulin Resistancementioning
confidence: 99%
“…However, other observations report discrepant results, showing that high-fat feeding in rats was associated with no variation (Atgié et al 1993, De Feyter et al 2008a or even a higher mitochondrial capacity (Hancock et al 2008), and IR could be related to incomplete intramitochondrial β-oxidation (Koves et al 2008). Several studies show that insulin resistance arises when mitochondrial function is unaffected or even improved , Ara et al 2011, Boudina et al 2012, or conversely that impaired mitochondrial functioning alone does not cause insulin resistance (Wredenberg et al 2006). These latter findings data seem to indicate that, at least in rodents, consumption of high-fat diet is not always accompanied by mitochondrial dysfunction, but rather leads to improved mitochondrial oxidative capacity and/or biogenesis (Gómez-Pérez et al 2012, Wessels et al 2015, even in the presence of IR.…”
Section: Mitochondrial Dysfunction In Insulin Resistancementioning
confidence: 99%
“…Some problems with these and other previous strain comparisons are the use of diverse HFDs varying in lipid and carbohydrate content and the investigation of limited variables that may underpin the development of metabolic disease and importantly some contradictory findings. For example, FVB/N mice have been characterised as both obesity-prone [6] and obesity-resistant [3], with similar contradictory observations reported for DBA/2 mice [1,7]. The C57BL/6 mouse strain is generally suggested to be the best strain for studying metabolic disease.…”
Section: Introductionmentioning
confidence: 98%
“…However, when creating genetically manipulated mice, consideration must be given to the genetic background on which the mouse is created and differences in metabolic phenotype that might be associated with gene manipulation on mixed genetic backgrounds. Several previous studies have shown that mouse strains can differ substantially in their metabolic phenotype under normal low-fat diet (LFD) conditions and in response to a high-fat diet (HFD) [1][2][3][4][5]. Some problems with these and other previous strain comparisons are the use of diverse HFDs varying in lipid and carbohydrate content and the investigation of limited variables that may underpin the development of metabolic disease and importantly some contradictory findings.…”
Section: Introductionmentioning
confidence: 99%
“…In healthy male subjects, high-fat feeding for 3 days was sufficient to reduce mRNA levels of PGC1α, PGC-1β and several other mitochondrial genes in skeletal muscle [107]. Similarly, genetic, or high-fat diet-induced obesity and insulin resistance in rodents has been reported by several groups to reduce mitochondrial gene expression, protein expression and mitochondrial respiration in skeletal muscle [107][108][109][110][111]. Providing additional evidence of a link between mitochondrial dysfunction and insulin resistance is the fact that antiretroviral therapy used to suppress human immunodeficiency virus infection causes insulin resistance in association with mtDNA copy number [112].…”
Section: Mitochondrial Dysfunction In Muscle and Its Association Withmentioning
confidence: 86%